'Our Forest School isn't just the trees.' Forest Schools: micro-communities for social and emotional development. Issue 2 (3rd April 2023) - Blackham, L.; Cocks, A.; Bunce, L. Taylor
ABSTRACT: Forest School provision is a growing phenomenon in the UK due to its perceived impact on participant learning and wellbeing. This study sought to understand the impact of Forest School provision on the social and emotional development of participants using practitioner's reflections. Semi-Structured interviews with six qualified Forest School Leaders explored practitioner experiences working with children and young people. A thematic analysis with a social-constructionist epistemology revealed three interrelated themes, which are inherent in the Forest School ethos. These themes show Forest Schools to be micro-communities constructed by participants. The study concluded that Forest School micro-communities are established by each Forest School that is formed. These micro-communities contribute to the social and emotional development of children and young people through the construction of a shared space, fostering a sense of community and a shared power paradigm between leaders and participants.